What is the effect of a shoulder-strengthening program to prevent shoulder pain among junior female team handball players? - Sommervold, M.; Østerås, H. (Open Access Journal of Sports Medicine, 2017)
Excessively high stresses are applied to the shoulder joint of handball players, mainly caused by overhead throwing. Shoulder pain is a significant problem among junior female team handball players and both male and female top-level team handball players in Norway. Method: A randomized selection was performed among the best female junior teams (J 16) in the Trøndelag region of Norway in the 2014-2015 season. Three teams were randomized to the intervention group and three teams to the control group. Players in the intervention group (n=53) participated in a seven-month, three-times-a-week shoulder-muscle strength-training program, while those in the control group (n=53) participated in a comparable handball training, but did not conduct any specific strength training during the season. Results: A strength-training program had no effect on the prevention of shoulder pain. Overall, the players reported shoulder pain, but graded the pain low on visual analog scale (VAS). Both the intervention group and the control group reported pain under 1 on VAS at baseline and posttest, and there was no significant difference within or between the groups when it came to the intensity of pain reported on VAS. A significant difference (p<0.048) was found between the groups on the sport-specific part of the quick-Disability of the Arm, Shoulder and Hand (DASH) form, but it did not fulfill the minimal demand to change and the players scored it low, something that indicates little functional problems when it comes to team handball. The intervention group was significantly stronger (p<0.008) on the push-ups test compared to the control group on the posttest. The intervention group increased the number of push-ups from 3.1 to 6.4, while the control group went from 2.3 to 3.6. Aside from this, there were no significant differences in between the groups. Conclusion: A shoulder-strengthening program had no effect on the prevention of shoulder pain among junior female team handball players.